The Level of Effectiveness of Online Marketing to the Customers Loyalty of Jcj Seat Zone General Upholstery in Quezon City: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The purpose of the study is to determine the level of effectiveness of online marketing to thecustomer's loyalty to JCJ Seat Zone General Upholstery in Quezon City in terms of age,gender, and employment status.The result of the study reveals that the majority of respondents are employed between theages of 21 and 30 years old; the majority of female respondents answered that the desiredfabric and materials are followed, and the majority of male respondents answered that theycommunicate effectively and imparts thorough knowledge about the offered product andservices in terms of brand positioning. In terms of quality expectation, the majority of femalerespondents answered that providing excellent service to the customer, knowledge, courtesyof employees, and their ability to convey trust and confidence are ethical, well-managed, andaccurate services. The majority of male respondents answered that providing excellentservice to the customer, products, and services at the given time, knowledge and courtesy ofemployees, and their ability to convey trust and confidence are ethical. In terms of productdurability, the majority of female respondents answered that the quality of the product issuperb and can go through frequent usage (daily usage). The majority of male respondentsanswered that they can go through frequent usage (daily usage). “How do females andmales assess the level of effectiveness of online marketing to the customer's loyalty in termsof brand positioning, quality expectation, and product durability? Female “Strongly Agree”and male “Agree.” The problems encountered by JCJ Upholstery are delayed supportresponse, lack of skills and experience in the field of marketing, and being inactive on socialmedia channels.The researchers recommend to the owner of JCJ General Upholstery to help them improveand attract more customers; they should be active on social media by appointing skilledemployees when it comes to online marketing techniques and strategy.
Keywords: Business Administration